Preparing International Students for Re-entry Transition - Arthur, Nancy (Canadian Journal of Counselling and Psychotherapy, 2007)
International students are a unique population of people in cross-cultural transition. More attention has been paid to their initial adjustment to life in a foreign country than their re-entry experiences of leaving the host country to return home. Counsellors are an integral part of campus support services to assist international students to manage cross-cultural transitions. Re-entry counselling can support international students to examine their transition experiences, provide education about re-entry, and help to develop anticipatory coping strategies. An example of a workshop is described using critical incidents as a method of generating discussion about leaving the host country and preparing for life at home.